1994
DOI: 10.1111/j.1365-3059.1994.tb00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Peronospora viciae expressed as differential colony growth in two cultivars of Pisum sativum

Abstract: Peronospora viciae sporulated frequently following localized inoculation of leaflets of Pisum sativum cv. Krupp Pelushka but rarely on cv. Early Onward (60 and < 1% of plants respectively). Similar results were obtained following inoculation of seedling shoot apices. The proportions of sporangia that germinated, formed appressoria, invaded via stomata or cuticle, and established colonies, were similar on leaflets of both cultivars. After 2 days, total hyphal lengths of most colonies were greater than 100 μm (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In P. manshurica on soybean, virtually all penetration was via anticlinal cell walls (Riggle, 1977), whist in P. destructor on onion penetration was reported to be entirely via stomata (Kofoet and Zinkernagel, 1991). Approximately 20% of infections by P. viciae on pea leaves were via stomata, in experiments that compared two cultivars with a two-fold difference in the number of stomata per unit area and in the total circumference of aperture available for penetration (Clark and Spencer-Phillips, 1994). This suggested that Figure 2.…”
Section: Conidia and Sporangiamentioning
confidence: 94%
See 4 more Smart Citations
“…In P. manshurica on soybean, virtually all penetration was via anticlinal cell walls (Riggle, 1977), whist in P. destructor on onion penetration was reported to be entirely via stomata (Kofoet and Zinkernagel, 1991). Approximately 20% of infections by P. viciae on pea leaves were via stomata, in experiments that compared two cultivars with a two-fold difference in the number of stomata per unit area and in the total circumference of aperture available for penetration (Clark and Spencer-Phillips, 1994). This suggested that Figure 2.…”
Section: Conidia and Sporangiamentioning
confidence: 94%
“…Autofluorescence is probably due to deposition of phenolics in the cell walls (Stumpf and Heath, 1985). Substantial numbers of these cells have been seen in a compatible interaction between P. viciae and the pea cv Krupp Pelushka, in which the cells were only lightly stained by Trypan Blue (although colonies within this interaction had less necrotic cells per length of hyphae than colonies within the resistant cv Early Onward; Clark and Spencer-Phillips, 1994). It is not known whether these cells were undergoing necrosis as part of a hypersensitive response, or whether they were undergoing a mild reaction which resulted in recovery and maintenance of the compatible interaction.…”
Section: Physiology and Biochemistrymentioning
confidence: 97%
See 3 more Smart Citations